Kemas Ulang Informasi Budidaya Jamur Tiram Nagari Sungai Buluh Kabupaten Padang Pariaman - Irwan, Endricke Aditya; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
This paper aims to describe the re-packaging of information on oyster mushroom cultivation Nagari Sungai Buluh Padang Pariaman. The method used is descriptive research method with data collection through interview. Data collection through interviews conducted with farmers oyster mushroom business Nagari Sungai Buluh Padang Pariaman. Based on the discussion can be concluded the stages in packing the information of oyster mushroom cultivation Nagari Sungai Buluh Padang Pariaman District as follows: (1) Identify the needs of users, (2) Finding the needed resources, (3) Information gathering, (4) Packaging of information, (5) Determine the form of packaging, (6) Make editing, (7) Printing the packagingKeyword: Repacking, Oyster Mushroom